P073: Single and dual vs. standard triple agent regimens for HIV post-exposure prophylaxis in the sexual assault victim population. (15th May 2017) - Kumar, T.; Sampsel, K.; Stiell, I.G.
Abstract : Introduction: Although Tenofovir/Emtricitabine was approved in 2012 as a single-agent regimen for pre-exposure prophylaxis, there have been no studies to our knowledge that demonstrate the efficacy of single and dual agent regimens in post-exposure prophylaxis. Our goal was to compare outcomes of post-exposure prophylaxis with single and dual agent regimens versus triple therapy in victims of sexual assault.Methods: This was a before and after cohort study of patients seen by the Sexual Assault and Partner Abuse Care Program (SAPACP) at the Ottawa Hospital. We reviewed charts of patients seen by the SAPACP from Jan. 1-Dec. 31 2013, when triple therapy was usual care, and Jan. 1-Dec. 31 2015, after the introduction of alternative regimens. Patients who were deemed high risk or who did not get initial treatment at the SAPACP were excluded. Our primary outcome was the number of patients who completed the entire 28-day post-exposure prophylaxis regimen. Secondary objectives were to assess HIV seroconversion rates and patient reported side effects.Results: Six hundred-thirty charts were reviewed, and 429 were included in the study. Baseline characteristics were similar between the two years. We found no significant difference in completion rates of HIV post-exposure prophylaxis between the two cohorts (50.5% vs. 51.6%). However, we did note a decrease in reported side effects in the 2015 cohort (72.2% vs. 17.6%, p<0.0001). In our secondary analysis, we compared all patients in all years who received triple therapy (N=128) versus those who received alternative single or dual agent regimens (N=47). We found that the alternative regimen group had a higher completion rate (66.0% vs. 42.2%; p=0.03), and a dramatic decrease in rate of reported side effects (19.1% vs. 53.9%; p<0.0001). Specifically, we saw decreased reported rates of nausea (12.8% vs. 36.7 %), constipation (0% vs. 7.9%), diarrhea (2.1% vs. 21.1%), mood changes (0% vs. 10.9%), headache (2.1% vs. 16.4%), and fatigue (6.4% vs. 26.6%). There were no HIV seroconversions in either group.Conclusion: Our results suggest that single and dual agent HIV post-exposure prophylaxis regimens are better tolerated by patients and associated with higher rates of completion than triple therapy, and should be considered as stand-alone therapy in the sexual assault victim population.